2021
DOI: 10.1042/cs20201394
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol metabolism: a new molecular switch to control inflammation

Abstract: The immune system protects the body against harm by inducing inflammation. During the immune response, cells of the immune system get activated, divided and differentiated in order to eliminate the danger signal. This process relies on the metabolic reprogramming of both catabolic and anabolic pathways not only to produce energy in the form of ATP but also to generate metabolites that exert key functions in controlling the response. Equally important to mounting an appropriate effector response is the process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 181 publications
(202 reference statements)
0
44
0
Order By: Relevance
“…As pointed out earlier, cholesterol has the potential to control innate immunity with respect to IFN responses. Additionally, there is growing awareness that its anabolism and its derivatization into oxysterols or BAs mediate central aspects of inflammation ( Spann et al, 2012 ; Perucha et al, 2019 ; Willinger, 2019 ; Cardoso and Perucha, 2021 ). How and if cholesterol trafficking to these organelles affects these mechanisms remains largely elusive so far.…”
Section: Endosomal Cholesterol Trafficking As Shared Feature In Viral Infectionsmentioning
confidence: 99%
“…As pointed out earlier, cholesterol has the potential to control innate immunity with respect to IFN responses. Additionally, there is growing awareness that its anabolism and its derivatization into oxysterols or BAs mediate central aspects of inflammation ( Spann et al, 2012 ; Perucha et al, 2019 ; Willinger, 2019 ; Cardoso and Perucha, 2021 ). How and if cholesterol trafficking to these organelles affects these mechanisms remains largely elusive so far.…”
Section: Endosomal Cholesterol Trafficking As Shared Feature In Viral Infectionsmentioning
confidence: 99%
“…In affected animals, AEs were preceded by an elevation of inflammatory markers including NLR ratio, CRP, MCP-1, IL-6 with hypoalbuminemia and hypocholesterolemia related to the high-energy demand in cachexia-associated systemic inflammation. [95][96][97][98] These markers were strongly correlated with the severity of AEs. This chronic, systemic inflammation-mediated catabolism worsened with increasing time posttransplant, was associated with increased expression of CRP and CD40 in livers and kidneys of xenoislet but not alloislet recipients, and appeared unresponsive to maintenance immunosuppression with CTLA4Ig, tacrolimus, and rapamycin.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, the roles of cholesterol in the immune system have been discussed. Cardoso et al indicated that the level of cholesterol could respond to immune responses (including innate and adaptive immune cell systems) [ 45 ]. Intriguingly, a gene of C. burnetii encoding a sterol-modifying enzyme was determined to be critical for the survival in phagolysosome-like vacuoles and essential for pathogenesis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%